Analysis of Microplastic Contamination in Vaname Shrimp (Litopenaeus Vannamei) with Different Cultivation Methods - Puji Hastuti; Asih Fitriana Dewi; Defri Yona; Muhammad Mahmudi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Vaname shrimp cultivation is inseparable from the use of plastic. Plastic will fragment into microplastics and pollute the environment. Water sources and cultivation methods are often the source of microplastics entering the cultivation environment. This study aims to determine microplastic pollution in three different cultivation methods, seen from the presence of microplastics in water, sediment, commercial feed, and whiteleg shrimp. Sampling was carried out for three months of December 2024 - February 2025 by testing microplastics in water, sediment, feed, gill organs, and the digestive tract of whiteleg shrimp during one cultivation cycle. The microplastics found amounted to 1,593 particles, 877 particles in water, 561 particles in sediment, 53 particles in feed, and 102 particles in shrimp samples. The microplastics found were in the form of films, fragments, fibers, and pellets with sizes between 10-600 micrometer. The average abundance of microplastics in water and sediment fluctuates depending on geographical and weather conditions. Microplastics in feed indicate the presence of microplastic sources from the monthly feeding process. Meanwhile, the abundance of microplastics in shrimp accumulates every month. The differences in microplastic abundance in the three methods indicate the presence of microplastic pollution originating from cultivation equipment, commercial feed, and water sources that have been contaminated with microplastics.